POLYCENTRICITY AND COMMUTING. AN APPLICATION TO METROPOLITAN AREAS IN THE SOUTH OF POLAND - Elżbieta Zuzańska-Żyśko (Acta Geobalcanica, 2018)
Commuting is an element of functional interrelations in metropolitan regions. They determine the nodes of a settlement system and portray economic attractions. The purpose of the article is to designate the dominant directions of commuting in a polycentric and post-industrial region – the Górnośląska-Zagłębiowska Metropolis in the south of Poland. The article analyses the influence of urban structures on commuting in the period of 2006 and 2011. The Nystuen-Decey method has been employed in order to grasp the spatial patterns of work places in the metropolitan area. The results of examinations prove that communing is very complex and creates the system of social economic interrelations with the main centre of Katowice.